ANALYSIS OF THE ASSOCIATION BETWEEN BIOSECURITY PRACTICES AND DISEASE PREVALENCE IN GOATS IN PALANGKA RAYA - Ardi Sandriya; Satrio Wibowo; Nur Hafidzah Devi Kartika (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Goats are a livestock commodity that provides animal protein, supports food security, and offers income opportunities because of their relatively short production cycle. Successful goat farming relies heavily on effective sanitation and hygiene practices, which are crucial for preventing disease transmission and maintaining optimal productivity in the herd. This study aimed to examine the relationship between farmers’ characteristics (age, education, and farming experience) and the level of biosecurity and hygiene implementation, as well as their impact on disease occurrence in goat farms in Palangka Raya City, Indonesia. The study was conducted in August 2025 and involved 10 goat farmers who were surveyed, interviewed, and observed in the field. Data were analyzed using a scoring system and chi-square test (χ²). The results indicated that age and farming experience had no significant effect (p>0.05) on biosecurity and hygiene practices. In contrast, education significantly influenced the implementation of isolation biosecurity, health management, and hygiene (p<0.05). Moreover, farms with higher biosecurity and hygiene levels showed significantly lower disease occurrence. These findings underscore the importance of education in promoting effective biosecurity and hygienic practices. Enhancing farmer knowledge through targeted training and extension programs is essential for reducing disease risks, improving livestock health, and supporting the sustainability of goat farming in Palangka Raya.